2022
DOI: 10.1111/jocs.16876
|View full text |Cite
|
Sign up to set email alerts
|

Coronary unroofing does not fits all anomalous aortic origin of coronary arteries

Abstract: Introduction: Anomalous aortic origin of coronary artery (AAOCA) is the second leading cause of sudden cardiac death in children and young adults. Intramuralinterarterial course is the most frequent anatomic variation and coronary unroofing is widest adopted for surgical management. Symptoms recurrence is described regardless of the technique used. This study aims to describe how an anatomic patient-centered approach aimed to restore a normal coronary artery take-off is associated with symptoms resolution. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Unroofing techniques may cause atherosclerosis and scarring in the long term due to significant manipulation of the coronary artery (14). In a study conducted by Arcieri et al it was suggested that coronary unroofing is not a technique suitable for all anatomic subtypes of anomalous origin of coronary arteries and that the selection of a surgical technique must be done according to a specific patient anatomy-based approach (15). In our case, the RCA had an interarterial and intramural course with a stenotic ostium.…”
Section: Discussionmentioning
confidence: 73%
“…Unroofing techniques may cause atherosclerosis and scarring in the long term due to significant manipulation of the coronary artery (14). In a study conducted by Arcieri et al it was suggested that coronary unroofing is not a technique suitable for all anatomic subtypes of anomalous origin of coronary arteries and that the selection of a surgical technique must be done according to a specific patient anatomy-based approach (15). In our case, the RCA had an interarterial and intramural course with a stenotic ostium.…”
Section: Discussionmentioning
confidence: 73%
“…Echocardiography can usually provide this information but may be limited in older patients and prone to false negatives. 55,56 Coronary imaging is especially indicated in repaired CHD involving coronary reimplantation as TGA treated by arterial switch operation. Major complications in this setting include coronary stenosis at anastomotic sites, neo-aortic dilation, neo-pulmonary or branch pulmonary artery stenosis, and valvular or ventricular dysfunction.…”
Section: Coronary Arteriesmentioning
confidence: 99%
“…In addition, neither echocardiography nor CMR can consistently evaluate distal coronary anatomy. 55,56,[58][59][60] CMR may also be an option and can provide important information on additional findings, including global and regional function, perfusion, and viability. Because late coronary complications are reported to be very low, routine screening of coronary arteries is still questionable in TGA patients post atrial switch; therefore, CMR is generally indicated to assess pulmonary trunk and branches, ventricular volumes, FE, aortic root dilatation, and regurgitation and is an alternative technique to assess myocardial perfusion and possibly coronary artery compromise, when clinically indicated.…”
Section: Coronary Arteriesmentioning
confidence: 99%
See 2 more Smart Citations